2018
DOI: 10.1021/acsami.7b19646
|View full text |Cite
|
Sign up to set email alerts
|

EQE Climbing Over 6% at High Brightness of 14350 cd/m2 in Deep-Blue OLEDs Based on Hybridized Local and Charge-Transfer Fluorescence

Abstract: Three deep-blue emitters PPi-Pid, PPi-Xid, and PPi-Mid based on a novel conjugated system phenantroimidazole-π-indolizine have been designed and synthesized. Here, indolizine with appropriate π-conjugation length was used as the acceptor profited from its high-photoluminescence quantum yield and good electron-withdrawing ability. Fluorescent organic light-emitting diodes (OLEDs) based on PPi-Pid, PPi-Xid, and PPi-Mid achieved deep-blue emissions with the Commission Internationale de L'Eclairage coordinates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…maintained at 3.01%). The three deep-blue emitters PPi-Pid, PPi-Xid, and PPi-Mid based on the novel conjugated system phenantroimidazole-π-indolizine were reported by Zhang [58]. Indolizine, with an appropriate π -conjugation length, was used as the acceptor due to its high PLQY and good electron-withdrawing ability.…”
Section: Pi-based Fluorescent Materialsmentioning
confidence: 99%
“…maintained at 3.01%). The three deep-blue emitters PPi-Pid, PPi-Xid, and PPi-Mid based on the novel conjugated system phenantroimidazole-π-indolizine were reported by Zhang [58]. Indolizine, with an appropriate π -conjugation length, was used as the acceptor due to its high PLQY and good electron-withdrawing ability.…”
Section: Pi-based Fluorescent Materialsmentioning
confidence: 99%
“…However,mosto fthem would internally generate intramolecular charge transfer (ICT), leading to energyc onsumption and the redshift of emission. [18] Recently, Su et al reported as eries of new fluorescent emitters, one of which realized an EQE of 4.22 %a t1 0000 cd m À2 .H owever,t he CIE coordinates of (0.145, 0.104) did not meet the NTSC requirements. [19] Lu et al reported deep-blue fluorescent OLEDs based on anthracened erivatives, which possessed an EQE of 3.21 %a t1 0000 cd m À2 with CIE coordinates of (0.15, 0.07).…”
Section: Introductionmentioning
confidence: 99%
“…We have developedb lue electroluminescent materials with the IP isomer. [18] Moreover,t he frontier molecular orbitals( FMOs) and energy levels of IP,T P, and BI are shown in Figure 1. In practice, [1,2,4]triazolo[1,5-a]pyridine( TP) and 1 H-benzo[d]imidazole (BI) have been employed to construct deep-blue light-emitting materials [26][27][28] owing to their lowest unoccupied molecular orbital (LUMO) levels, which are essential to determinetheir electron-withdrawing ability;s tronger electron-withdrawing ability depends on ad eeper LUMO level.…”
Section: Introductionmentioning
confidence: 99%
“…The external quantum efficiency (EQE) of D‐A type or D‐π‐A type blue fluorescent emitters was generally below 5% due to spin statistics limitation [ 23 ] and the blue emitters with above 5% EQE were mainly limited to pyrene or imidazole type materials. [ 24–31 ] Besides, the full width at half maximum (FWHM) was above 50 nm [ 31–35 ] and only very few emitters showed FWHM below 40 nm. [ 24 ] However, the D‐A and D‐π‐A type emitters also suffered from color purity due to intramolecular charge transfer (ICT) as it resulted in red‐shifted emission with broad spectrum.…”
Section: Introductionmentioning
confidence: 99%